2012
DOI: 10.1186/1479-5876-10-125
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of explant tumorgraft models derived from fresh patient tumor tissue

Abstract: BackgroundThere is resurgence within drug and biomarker development communities for the use of primary tumorgraft models as improved predictors of patient tumor response to novel therapeutic strategies. Despite perceived advantages over cell line derived xenograft models, there is limited data comparing the genotype and phenotype of tumorgrafts to the donor patient tumor, limiting the determination of molecular relevance of the tumorgraft model. This report directly compares the genomic characteristics of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 40 publications
2
48
2
1
Order By: Relevance
“…Tumorgrafts typically maintain the fundamental genotypic and phenotypic features of the original tumor and have been shown to be highly predictive of patient response to therapies (35,36). Even in the limited number of tumorgrafts included in this study, initial findings are revealing.…”
Section: Kras Status Predictsmentioning
confidence: 63%
“…Tumorgrafts typically maintain the fundamental genotypic and phenotypic features of the original tumor and have been shown to be highly predictive of patient response to therapies (35,36). Even in the limited number of tumorgrafts included in this study, initial findings are revealing.…”
Section: Kras Status Predictsmentioning
confidence: 63%
“…Therefore, new approaches to personalized cancer therapy are necessary to match individual tumors with effective agents. Evidence from recent studies has demonstrated that tumorgrafts, or patient-derived xenografts (PDX), established by engrafting patient tumors into immunocompromised mice, preserve the structural components, heterogeneity, gene expression pattern, and genetic mutations of the original tumors (2-4). These features are maintained through several generational passages of the tumorgrafts in mice (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…The failure of preclinical pipelines for therapeutic development based on mononuclear layers of tumor has led to a resurgence in the use of patient-derived tumor xenograft (PDX or tumorgrafts) models for preclinical evaluation of novel chemotherapeutic strategies [13]. Human tumorgraft models are obtained by the transplantation of primary tumor fragments straight from the operating room into an immunodeficient mouse.…”
Section: Resurgence Of Tumorgrafts For Cancer Research and Biomarker Dementioning
confidence: 99%